Totality from Interiority: The Nineteenth-Century Russian Novel as Epic in Georg Lukàcs's The Theory of the Novel. (May 2014) - Dantzlerward, Alexandra
<x content-type="archive" xml:space="preserve">Abstract</x> In The Theory of the Novel, Georg Lukàcs's (1885–1971) approach to the nineteenth-century Russian novel evidences underlying conflict: without presenting theoretical justification, Lukàcs continually refers to these works as 'epic'. Yet according to the opposition he creates between novel and epic, the idea of a work's belonging to both genres — even peripherally — appears paradoxical. This article explores the possibility that from Lukàcs's approach within the Theory, the particular history and characteristics of the nineteenth-century Russian novel make it genuinely qualify for the seemingly-impossible classification of renewed epic; hence his continual implication that this is its true genre. Lukàcs's treatments of nineteenth-century Russian novelists mentioned in the Theory are examined as support for this reading.